DEVELOPMENT OF A LOCATION AND WIFI-BASED SMART ATTENDANCE SYSTEM: A CASE STUDY OF EMPLOYEES AT UNIVERSITAS PGRI YOGYAKARTA - Khairul Nur Syahlan; Wibawa; Puji Handayani Putri (JTH: Journal of Technology and Health, 2025)
The development of information technology has brought significant changes in various aspects of life, including employee attendance systems. Conventional fingerprint-based attendance still has several issues, such as dependence on physical contact, which poses a risk for disease transmission, and accuracy problems due to the cleanliness and humidity of fingerprints. Therefore, this research aims to design and implement an attendance system based on location and WiFi, with the addition of face recognition technology to improve efficiency and accuracy in recording employee attendance at the Universitas PGRI Yogyakarta. The research methods used include literature study, interviews, and system testing through alpha testing with 20 respondents. The results show that this attendance system received positive feedback from users, with 98% of respondents stating that the system's interface was good, 90% evaluating the system as working optimally, and 89% expressing overall satisfaction with the user experience. This system is able to reduce the potential for fraud, improve attendance accuracy, and simplify the data recap process. However, there are some challenges in implementation, such as reliance on network connectivity and GPS accuracy, as well as difficulties in facial recognition under certain lighting conditions. Therefore, further development is needed, such as improving network stability, optimizing face recognition technology, and providing socialization and training for users. With the results obtained, this system is expected to be an effective solution to improve the efficiency and accuracy of employee attendance in the workplace.